The effectiveness of a psychoeducation intervention delivered via WhatsApp for mothers of children with autism spectrum disorder (ASD) in the Kingdom of Saudi Arabia - Hemdi, Alyaa (2017)
Parents of children with autism spectrum disorder (ASD) experience numerous challenges caring for their children. Research shows that those parents, and specifically mothers, suffer from high levels of stress and poorer well-being compared to parents of children with other disabilities. Developing and evaluating interventions to help enhance their well-being and their interaction with their children is recommended (NICE, 2013). Parenting interventions have been shown to be efficacious for parents of children with ASD , yet practical barriers may have an impact on their widespread uptake (McConachie & Diggle, 2007). Self-help parenting interventions with minimal therapists’ support, which have the potential to overcome barriers to adherence, have been used with parents of children with other neurodevelopmental disorders. However, there is limited evidence evaluating these interventions and their effectiveness for parents of children with ASD. Moreover, most parenting interventions for parents of children with ASD focus on developing the parents’ abilities to enhance specific skills in their children, while only few include psychoeducation components addressing knowledge about ASD and parental well-being. The main aims of this thesis were to understand the impact of having a child with ASD on parental functioning both internationally and for Saudi Arabian mothers and to then develop and evaluate both quantitatively and qualitatively the effectiveness of a brief psychoeducation intervention for mothers of children with ASD in the Kingdom of Saudi Arabia (KSA). Chapter One provides an introduction to ASD including its current definition, diagnosis, co-morbidities, risk factors, and treatment options. In addition, it discusses the theoretical models related to parenting children with ASD, and autism within the context of KSA including gaps in current research there. Chapter Two (study one), presents a systematic review investigating the impact of having children with ASD on parental life. Autism was found to impact areas including response to ASD, parental well-being, relationships, positive perception, financial problems, and future worries. Differences in findings between mothers and fathers were identified. Chapter Three (study two) explores the unmet needs of Saudi mothers of children with ASD in KSA through a pilot qualitative study that used semi-structured interviews. Mothers expressed a range of issues and needs including feelings of lack of sufficient information about ASD, the need for parental training, shortage of quality ASD services, lack of fathers’ assistance, and stigma associated with having children with ASD. Moreover, mothers insisted that barriers such as lack of transportation add to their burden. Chapter Four (study three) presents a meta-analysis evaluating the effectiveness of parenting interventions on parental functioning of parents of children with ASD. Analyses revealed that parenting interventions are effective in enhancing parental well-being (stress, depression, and anxiety), parenting practices, and in increasing parents’ sense of competence SOC. Chapter Six (study four) delivers the findings from a small-scale randomised controlled trial (RCT) investigating the effectiveness of a self-help psychoeducation intervention with minimal therapists’ support, delivered via WhatsApp for mothers of children with ASD in KSA. The intervention was successful in reducing maternal reports of stress, depression, ASD symptoms, and child behaviour problems. Change of clinical significance was minimal and limited to maternal depression. Chapter Seven (study five) describes a qualitative study that evaluates the acceptability and views of mothers who participated in the trial in Chapter Six. Mothers had positive views of the intervention and many of them were actively engaged in the intervention and discussed new parenting skills and behaviours that they had acquired. Finally, Chapter Eight provides a general and overall discussion of the thesis findings, including a summary of the findings of all the studies within the thesis. In addition, methodological strengths and considerations, clinical implications, and direction for future research are discussed. Collectively, the studies within this thesis provided evidence for the effectiveness of self-help psychoeducation parenting intervention with minimal therapist support and delivered via a virtual medium for mothers of children with ASD in KSA indicating that such interventions may have a place in future routine care.